2010
DOI: 10.1210/jc.2009-2392
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance Is Associated with Glycemic Control, the Dose of Aspirin, and Obesity in Type 2 Diabetes Mellitus

Abstract: These data suggest that glycemic control, obesity, and the dose of aspirin have influence on AR in diabetic subjects. Further studies with larger groups are needed to clarify the role of glycemic control on AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 16 publications
4
32
2
1
Order By: Relevance
“…In most of these studies, an association between aspirin resistance and elevated HbA1c and increased fasting serum glucose levels was reported in diabetic patients [33,34,35]. The present study also found that fasting serum glucose level was a risk factor for aspirin resistance.…”
Section: Discussionsupporting
confidence: 81%
“…In most of these studies, an association between aspirin resistance and elevated HbA1c and increased fasting serum glucose levels was reported in diabetic patients [33,34,35]. The present study also found that fasting serum glucose level was a risk factor for aspirin resistance.…”
Section: Discussionsupporting
confidence: 81%
“…statins). [33,51,53] Indeed, 21-44% of patients [54][55][56][57][58] with diabetes display reduced laboratory responses (e.g. reduced TXA 2 production and platelet sensitivity) to antiplatelet therapies.…”
Section: Aspirin: Antiplatelet Effects and Pharmacokineticsmentioning
confidence: 99%
“…Other possible mechanisms leading to enhanced platelet reactivity under hyperglycemia include osmotic effect of glucose, increased activation of protein kinase C and decreased activation of nitric oxide (NO) - cyclic guanosine monophosphate (cGMP) - cGMP-dependent protein kinase pathway [1517]. These assumptions are supported by clinical studies demonstrating relationship between HAPR and inadequate glycemic control, as well as in vitro studies showing enhanced platelet activation, assessed using flow cytometry, with increasing glucose concentrations despite incubation with ASA [6,7,1823]. Alongside with poor glycemic control, HAPR in DM2 patients has been linked to high triglyceride, total cholesterol and low-density lipoprotein (LDL) concentrations, as well as low high-density lipoprotein (HDL) concentration [18,20,24].…”
Section: Introductionmentioning
confidence: 99%